Pengaruh Advertising Above the Line, Personal Selling dan Brand Image terhadap Keputusan Pembelian Sepeda Motor Merek Honda Pada PT. Mertha Buana Motor Singaraja. - Made Dwi Ferayani; Gusti Nyoman Darmi Kusuma Dewi (ARTHA SATYA DHARMA, 2023)
The researcher conducted this study aiming to determine the implication relationship between Advertising Above The Line, Personal Selling and Brand Image on purchasing decisions for Honda motorcycles at PT. Mertha Buana Motor Singaraja. The research methodology was conducted using a quantitative approach. The data collection used a questionnaire instrument, the selection of respondents was carried out by incidental sampling, namely randomly with 94 respondents. The data analysis technique used was the SPSS model version 18. All the relationships studied showed significant results.